Ethanol production from mixtures of sugarcane bagasse and Dioscorea composita extracted residue with high solid loading. (June 2018) - Ye, Guangying; Zeng, Defu; Zhang, Shuaishuai; Fan, Meishan; Zhang, Hongdan; Xie, Jun
Graphical abstract: Highlights: Sugarcane bagasse and DER are sufficient raw material for cellulosic ethanol. Starchy DER mixed with sugarcane bagasse boost ethanol concentration and yields. The highest ethanol of 82.83 g/L could be obtained by fed-batch and surfactant. The co-fermentation presented a competitive form to economy of cellulosic ethanol. Abstract: Various mixing ratios of alkali pretreated sugarcane bagasse and starch-rich waste Dioscorea composita hemls extracted residue (DER) were evaluated via simultaneous saccharification and fermentation (SSF) with 12% (w/w) solid loading, and the mixture ratio of 1:1 achieved the highest ethanol concentration and yield. When the solid loading was increased from 12% to 32%, the ethanol concentration was increased to 72.04 g/L, whereas the ethanol yield was reduced from 84.40% to 73.71%. With batch feeding and the addition of 0.1% (w/v) Tween 80, the final ethanol concentration and yield of SSF at 34% loading were 82.83 g/L and 77.22%, respectively. Due to the integration with existing starch-based ethanol industry, the co-fermentation is expected to be a competitive alternative form for cellulosic ethanol production.